PERUBAHAN PENGHIDUPAN (LIVELIHOOD) PENYINTAS HUNTARA PASCA ERUPSI MERAPI DI JUMOYO MAGELANG - , umi lestari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cold lava flood is one of the effects of the eruption that caused many losses and problems for the citizens and government. It caused big problem for people around, both infrastructure and economic problems. The survivors from that disaster now living at shelter, that build by the government as a form of responsibility towards its citizens. New place and also new living are caused wide range of problem of living, especially livehood assets and structural problems. Researchers intend to find answers related to how changes in livelihoods of shelter lived survivors after the eruption of Merapi and how their social structures condition? The purpose of this study was to determine changes in livelihoods of shelter lived survivors and knowing the condition of the social structure of post-eruption survivors at Jumoyo Shelter Village, Magelang. This study used a qualitative descriptive approach that generates comparative analysis of Chambers and Conway on the concept of livelihoods with the conceptual framework of research. A purposive sampling technique in the determination of the informant in which researchers determined the informant in accordance with the purpose of research is obtaining relevant data from key informants, the coordinator of shelters to members of the shelters. Data collection techniques obtained through direct observation, interviews and documentation. Techniques of data analysis is done in several stages in conjunction with existing data collection and data reduction, presentation of data and inferences are often referred to as triangulation of data. The results of this study indicate a change in livelihoods shelter lived survivors in accordance with the concept of living that include livelihood assets such as social capital, human capital, physical capital, financial capital and natural capital. Livelihood is not immune from social modifications such as social relations, government and social organizations. Livelihood base of residents include: agriculture, animal husbandry, trade, mining, and services. Temporary housing conditions make people more at home and in shelters following the activities of NGOs such as YEU. In general, the condition of the social structure of society is affected by economic conditions, government policies and the trauma of the disaster. It can be concluded that the change of life is affected by external factors, namely natural disasters and the changes are not permanent. Volcanic disasters have an impact on the livelihood changes with damadge lavel befitting become of livelihood it source.